O ensaio jornalístico na revista Veja: uma análise multidimensional - Medeiros, Maria Assunção Silva (2008)
This work has as objective generality to make a multidimensional analysis in the genre journalistic assay, communicative genre that, beyond complex and multimodal, presents hybrid characteristics. Specifically, with the intention to propose defining criteria of the cited genre, this research looks for to establish differences and similarities between the assay and other genres of the same sphere, from the description and interpretation of used multimodal resources. The analysis of the formal, schematical and rhetorical resources identified in the formatting of the journalistic assay sample that the analyses are supported in the socio-semiotic and socio-rhetorical approaches. In the formal dimension, we contemplate elements that constitute design of the text, including the forms of representation from the typography, the colors, images, as well as the aspects communicative-linguistics: the modalization indices, the communicative operators and the category time; in the schematical dimension, we present the organizational structure, considering the rhetorical movements postulates for Swales (1990) and in the rhetorical dimension we observe the categories: who writes, for who it writes, on what it writes and where writes. The adopted methodologicals postulates are of qualitative nature and the procedure is documentary, data that in we are valid them written texts of this genre as analysis object. Corpus it is constituted by a composed sample for 14 extracted texts of a set of 173 propagated journalistic assays weekly for the magazine Veja, in the period between August of 2004 and January of 2008. The analysis of the data showed that the journalistic assay, object of this study, materializes through multiple symbolic representations and multiple subjects that turn since a small episode of the daily facts of great social relevance in the present time, of historical and cultural nature, nationwide or international. Used for the first time by Montaigne in 1580, to assign, in saying of the proper author, written fast on its life and historical events, which could nor be remembered later , the term `assay' was enriched with other specifications, of form to enclose the one that if they call scientific assay today, academic assay, journalistic assay and other types of specific assays. These denominations have to see with the enrollment of the members of diverse of practices communities, in virtue of the multiplicity of activities carried through in these spheres. The conclusions the one that we arrive had been the following ones: 1. the discursive genre is not a pure entity, in virtue of the multiplicity of situations where the sorts if insert in the social actions; 2. the institutions define the configuration of one definitive genre, also its proper assignment, since for backwards of all discursive genre a voice exists to discipline - institutional voice, and in the case of the assays for analyzed us, the institutional voice if it presents, really, as a defining trace; 3. the journalistic assay, for its multiple symbolic representations, multiple subjects and for passing explicit or implicit opinions of its author, resembles it other genres, being able, therefore, to be inserted in a colony of opinionatives genres